A Comparative Look at Advanced and Enhanced Clinical Radiography Practices in the UK and Denmark: - a discussion paper - Higgins, Robert; Pedersen, Malene Roland Vils (Radiography Open, 2025)
Radiography practice has evolved significantly in both the United Kingdom (UK) and Denmark during the last decade, driven by the need for greater clinical skills and improved patient care. Technological progress has resulted from both innovations in imaging modalities and the expansion of radiographers’ responsibilities such as the MRI with more advanced fields, going from film to digital imaging and the latest artificial intelligence (AI) revolution. By comparing the frameworks, educational pathways, and professional roles associated with enhanced and advanced practice in radiography in these two countries, we provide an overview of options for radiographers to pursue career options. By examining the similarities and differences, we aim to provide insights into how each country approaches the development and implementation of advanced and enhanced radiographic practices.